Prioridades parentais no cuidado domiciliar de recém-nascidos pré-termo e a termo - Agnes Flórida Santos da Cunha (2019)
INTRODUCTION: The first few weeks of a newborn at home are a time of adaptation for the family, who need to deal with basic care such as breastfeeding, bathing, sleeping and bonding with the baby. Knowing the parental priorities in this initial coexistence can contribute to the understanding of the needs in the newborns care. AIMS: Compare parental priorities in the care of preterm (PT) and full term (FT) newborns in the first two months after hospital discharge, identify changes in priorities over time and compare affordances in the home environment. METHOD: Parents of 44 newborns (22 FT and 19 PT) were followed up for two months after discharge from the hospital, with three longitudinal evaluations (7 days, 30 and 60 days). They reported demands on infant care through a semi - structured interview and responded to the Affordances in the Home Environment for Motor Development Infant Scale (AHEMD IS) to check the environmental affordances. RESULTS: We found similarities in the reports of priorities in the comparison between groups, except for 'Feeding', which presented more reports in the FT group, in the first evaluation. Changes in demands have occurred over time. Priorities 'Bath' and 'Beware of the Navel' have significantly reduced, and 'Health Care' increased reporting in both groups. 'Feeding' and 'Sleep' presented a reduction in reports in the FT group , and constancy in PT group. The 'Routine Adaptation' category increased significantly in the PT group. Priorities related to Cry, Diaper Changing, Child Supervision and Lap/ Affection had few reports. Environmental affordances were similar in the groups, with an increase of the domains Total Score and Gross-Motor Toys over time. CONCLUSION: The knowledge of the priorities of care-giving and environmental affordances of PT and FT allows the health team to set goals appropriate to the parental needs, as well as guide and improve the guidelines available.